Return of Sinamot Money from the Perspective of Al'adatu Muhakkamah (Analysis of the Decision of the Padangsidimpuan City Religious Court Number 129/Pdt.G/2015/PA.Psk) - Baskoro, Bayu; Fatimah, Fatimah; Khalid, Khalid (Law Development Journal, 2024)
This paper is a study on the return of sinamot money in the decision of the Religious Court by examining based on the perspective of the fiqh rule Al'adatu Muhakkamah, which examines the reality that the lawsuit for the return of sinamot money submitted to the Padangsidimpuan City Religious Court, by the Panel of Judges was partially returned, with considerations that contain justice, certainty and legal benefits and cannot be separated from the consideration that custom is the law "al-adatu muhakkamah". Marriage dowry in Mandailing and Batak customs is generally known as Sinamot/Tuhor, referred to as Sinamot or Marhata Sinamot because it is a sale and purchase between the male party (paranak) and the female party (parboru) or it can also be said to be a dowry. Marhata Sinamot is one of the traditional events at the wedding and aims to explore the extent of the burden that can be shouldered by both parties, namely the male and female parties, so that the marriage can be carried out. In the Compilation of Islamic Law, Article 1 letter d states that dowry is a gift from the prospective groom to the prospective bride, whether in the form of goods, money or services that are not contrary to Islamic law, in line with this in chapter V of the Compilation of Islamic Law from Article 30 to Article 38 all discuss dowry with the provision that the dowry belongs to the wife after being given by the husband, but interestingly Article 35 paragraph 1 regulates that a husband who divorces his wife qobla al dukhul is obliged to pay half the dowry determined in the marriage contract. However, the reality in the decision of case 129/Pdt.G/2015/PA.Psk in the case of a divorce suit with a counterclaim for a full return of the dowry, but the Panel of Judges partially granted it with the consideration that after the marriage the Plaintiff and the Defendant had never had conjugal relations and the Plaintiff's status was still a girl, so the judge did istinbath law using the qiyas method of Article 35 paragraph (1) of the Compilation of Islamic Law for the case of a divorce suit. In addition, the judge's consideration also prioritizes customary law in the Mandailing indigenous community. In the customs of the mandailing community, if the marriage does not take place but the sinamot money has been given, and the cause is from the prospective husband, the sinamot money is considered forfeited, but if the cause is from the woman, she is obliged to return the sinamot money in full or larger. The decision of the Religious Court has provided justice, certainty, and legal benefits for the parties by deciding to grant in part, because part of the sinamot money has been used for the benefit of the party. with this decision, it is very wrong to say that customary law and positive law intersect, because in various conditions customary law and positive law work hand in hand to realize legal objectives in the frame of court decisions. Exploring the law that lives in the midst of the community where the parties are litigating is important, considering that society and custom are two things that cannot be separated. Society has lived with customary law even long before positive law existed, so the correlation between the two is a requirement for a quality decision from the perspective of sociological considerations. This research is expected to be an academic study among legal practitioners and academics, that customary law, positive law and Islamic law can work together to realize legal goals.